Translocation and amplification of an X-chromosome DNA repeat in inbred strains of mice. - Disteche, C M (1987)
A 9-kb repetitive DNA fragment (70-38) located near the centromere of the mouse X chromosome is amplified and translocated to an autosome in different inbred strains of mice. In situ hybridization and hybrid cell studies showed that probe 70-38 is located only on the X chromosome in mouse strains A/J, AKR/J, BALB/cJ, CBA/J, C3H/HeJ, C57BL/6J, DBA/2J and SWR/J. However, in four other mouse strains the DNA sequence is found near the centromere of an autosome in addition to the X chromosome. This autosome differs among the mouse strains (chromosome 11 in C57BL/10J or ScSn, chromosome 13 in NZB/B1NJ and chromosome 17 in SJL/J and PO). In those strains where the repeated sequence is located on an autosome, it has been amplified to about 100 copies. Restriction enzyme digestion patterns suggest a common structure for 70-38 sequences in the different strains. The changes in copy number, restriction enzyme digestion patterns, and chromosomal location of 70-38 reflect a rapid genomic evolution inbred mouse strains.